Thermal Degradation of Polymer Blends, Composites and Nanocomposites - Visakh, P. M.; Arao, Yoshihiko (Engineering Materials,, 2015)
This book delivers a deep insight into thermal polymer degradation features and put a particular emphasis on blends, composites and nanocomposites. It examines the thermal stability and the mechanism of degrading for every class of polymer substances, and studies the effect on reinforcement to all classes. The book further explores the thermal stability when nano particles are added and summarizes the latest studies and application relevant results.This book offers a valuable reference source to graduate and post graduate students, engineering students, research scholars and polymer engineers from industry.